Data generated by a Monte Carlo based simple vessel simulation of the ASE qBOLD signal - Blockley, N; Stone, A; Holland, N; Berman, A (University of Oxford, 2019)
The data in this archive was generated using a Monte Carlo based numerical simulation of the extravascular blood oxygenation level dependent effect (BOLD) MRI signal. This data will underpin a forthcoming publication investigating systematic error in the asymmetric spin echo (ASE) quantitative BOLD (qBOLD) technique. Please reference this dataset if you use it in your work. Stone AJ, Holland NC, Berman AJL, Blockley NP. Data generated by a Monte Carlo based simple vessel simulation of the ASE qBOLD signal. Oxford University Research Archive 2019. See ORA record for DOI.